GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2017)
A dataset containing 165716 species occurrences available in GBIF matching the query: HasCoordinate: true TaxonKey: Pedicularis L. HasGeospatialIssue: false. The dataset includes 165716 records from 367 constituent datasets: 5 records from Bioimages. 11 records from CBDC: Cumbria Wildlife Trust: survey records from 1970 - 2007 of County Wildlife Sites.. 9 records from Merseyside BioBank (unverified). 36 records from NBIS Records to December 2016. 93 records from Marie-Victorin Herbarium (MT) - Plantes vasculaires. 13 records from Wicken Fen nature reserve species data held by The National Trust. 235 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 12 records from Phanerogamic Botanical Collections (S). 594 records from Jordal. 1 records from Herbier G. Garapin (BOUM). 77 records from University of Vienna, Institute for Botany - Herbarium WU. 222 records from Isle of Man wildlife records from 01/01/2000 to 13/02/2017. 144 records from Dorset SSSI Species Records 1952 - 2004 (Natural England). 62 records from Vascular Plants, Field notes, Agder naturmuseum (KMN). 94 records from Online Atlas of vascular plants 2012-2020. 2 records from IAC - Herbário do Instituto Agronômico de Campinas. 1 records from Caracterización Floristica del Páramo Tatamá. 4 records from Derbyshire Red Data List Plant Records 1930 - 2014. 75 records from Dorset Sites of Nature Conservation Interest (SNCI) species records pre 2000. 149 records from Naturalis Biodiversity Center (NL) - Botany. 5 records from PlutoF platform observations. 6 records from Herbario Nacional Colombiano (COL). 206 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 2 records from UTEP Plants (Arctos). 6 records from Nature Conservancy Council Oxfordshire Fen Survey 1983 (as held by Thames Valley Environmental Records Centre). 1371 records from Plant Specimen in Yunnan, China from Herbarium (PE),Institute of Botany, Chinese Academy of Sciences. 9 records from Computarización de las colectas del estado de Morelos depositadas en el Herbario HUMO de la Universidad Autónoma del Estado de Morelos. 239 records from LNHG Biological Records Dataset. 74 records from Species plots from the Norwegian Vegetation Mapping Programme. 1 records from University of Amsterdam (NL) - Páramo pollen reference collection. 1 records from Local BioBlitz Challenge 2013. 780 records from FLORIVON. 1166 records from Vascular plants in Denmark recorded under the The Nationwide Monitoring and Assessment Programme for the Aquatic and Terrestrial Environments (NOVANA). 118 records from Karplanter i vernet barskog og edelløvskog. 9 records from Herbario Universidad de Antioquia (HUA). 204 records from University of Alberta Vascular Plant Herbarium (ALTA-VP). 1226 records from Some Plant Specimens from KUN, IBSC, NAS Herbarium in China from 1900 to 1950. 256 records from Plant Specimen from Herbarium (CDBI) in China, Chengdu Institute of Botany, Chinese Academy of Sciences. 526 records from Shropshire Ecological Data Network database. 5 records from Inventaire National du Patrimoine Naturel : Flore de l'Ain. 741 records from Florabank1 - A grid-based database on vascular plant distribution in the northern part of Belgium (Flanders and the Brussels Capital region). 77 records from RECORD Vascular Plant Data. 4 records from Digitization of plant specimens from Rhoen and Vogelsberg (FLAD). 86 records from The digitization of plant specimens of NTU. 11 records from Staffordshire Wildlife Trust Nature Reserves Inventory. 2 records from Local Wildlife Site Surveys Berkshire. 1 records from PondNet data 2012-2014. 47 records from Inventaire National du Patrimoine Naturel : Atlas de la flore de Lorraine. 749 records from BioFokus. 2 records from Herbario Universidad de Caldas - FAUC. 2 records from Lowland lakeshore vegetation in Nord-Trøndelag, Norway. 119 records from Herbier Louis-Marie (QFA) - Collection de plantes vasculaires. 215 records from Vascular plant herbarium, Agder naturmuseum og botaniske hage. 4 records from Caracterización del hábitat y patrones de distribución del gorrión serrano (Xenospiza baileyi) en el sur del Valle de México. 67 records from Catálogo electrónico de especímenes depositados en el Herbario de la Universidad de Texas en Austin, Fase IV. 39 records from Dutch Foundation for Applied Water Research (STOWA) - Limnodata Neerlandica. 17873 records from Artportalen (Swedish Species Observation System). 30 records from Plant Specimen Database of Tama Forest Science Garden, Forestry and Forest Products Research Institute, Japan. 1 records from Flora of Słowiński National Park, Poland. 1 records from BBOWT Local Wildlife Sites Surveys 1994-2003. 20 records from Isle of Wight Notable Species. 3 records from Stabbetorp - Floristiske registreringer 2016. 3 records from InboVeg - NICHE-Vlaanderen groundwater related vegetation relevés for Flanders, Belgium. 247 records from Miscellaneous records held on the Cofnod database. 32 records from River Macrophytes Database. 2 records from Collection botanique Jaubert et Saul (BOUM). 93 records from Inventaire National du Patrimoine Naturel : Flore du Limousin. 373 records from Oskarshamn herbarium (OHN). 764 records from Données ONF Faune-Flore-Fonge. 7 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on the Skye Estate during October 1995 â October 2004.. 5 records from Norwegian Biodiversity Information Centre - Other datasets. 9 records from Bryophyte Survey of the Poole Basin Mires - NBN South West Pilot Project Case Studies. 2 records from BRFC Black Rock Forest Consortium Herbarium. 11 records from Australia's Virtual Herbarium. 1611 records from CSIC-Real Jardín Botánico-Anthos. Sistema de Información de las Plantas de España. 140 records from Vascular Plant Herbarium, UiB. 248 records from DBG Kathryn Kalmbach Herbarium. 23 records from Banco de Germoplasma del Jardín Botánico Atlántico. 12 records from Hertfordshire Flora Survey Records 1987-2005. 2 records from Natural History Museum Maastricht (NL) - Herbarium. 3573 records from Consortium of California Herbaria. 318 records from NRW Regional Data: all taxa (excluding sensitive species), West Wales. 1507 records from iNaturalist Research-grade Observations. 1 records from UCBG TAPIR Provider. 4 records from ARKO strandeng. 140 records from CONN. 17181 records from Other BSBI Scottish data up to 2012. 37 records from University of Lethbridge Herbarium (LEA). 7 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Vascular Plants. 4 records from Estonian Museum of Natural History. 1 records from Catálogo electrónico de especímenes depositados en el Herbario de la Universidad de Texas en Austin, Fase IV. 6 records from Collection botanique Le Grand A. (BOUM). 90 records from Vegetation data from sheep grazing experiment at alpine site in Hol, Norway. 30 records from NINA botanical collection. 53 records from National Trust Species Records. 426 records from Meadow and Pasture Inventory (SJV). 26 records from Flora acuática vascular del estado de Morelos, México. 1974 records from UAM Herbarium (ALA), Vascular Plant Collection (Arctos). 68 records from Finnish Floristic Database (Small Collections). 3 records from Estonian University of Life Sciences. 41 records from A common plants survey of vascular plants in South Northumberland and Durham, United Kingdom. 1 records from Siegen/ Gymnasium Am Löhrtor. 1 records from Plant Specimen from Herbarium (NAS) in China, Institute of Botany, Jiangsu Province and Chinese Academy of Sciences. 1 records from WildesMoor bei Schwabstedt. 1 records from GEO-Hauptveranstaltung im Nationalpark Bayerischer Wald. 2 records from Geneva Herbarium – De Candolle's Prodromus (G-DC). 104 records from Herbarium specimens of Société des Sciences Naturelles et Mathématiques de Cherbourg (CHE). 1964 records from Occurrence Data of Vascular Plants collected or compiled for the Flora of Bavaria. 1423 records from Phase 2 Lowland Grassland Survey of Wales. 10 records from Yorkshire Wildlife Trust - Non-sensitive records from all taxonomic groups. 1 records from Naturhistorisches Museum Mainz, Herbarium Oesau. 32 records from Naturhistorisches Museum Mainz, Feldbeobachtungsdaten Pflanzen. 594 records from SEWBReC Vascular Plants (South East Wales). 515 records from naturgucker. 1 records from Hatfield Forest species data held by The National Trust.. 85 records from Standing Waters Database - Scotland. 1 records from Plants, Bryophytes and Lichens recorded on the L젡nd Coire Dhorrcail Estate during June 2001.. 57 records from Gloucestershire Historic Wildlife Sightings prior to 1st Jan 2000. 1 records from KU Grensestasjon nord Sør-Varanger 2013 - Vegetasjon. 3649 records from Dutch Vegetation Database (LVD). 25280 records from INPN - Données flore des CBN agrégées par la FCBN. 10 records from Cartografía de vegetación a escala de detalle 1:10.000 de la masa forestal de Andalucía. 1 records from The Fungal Collection at the Senckenberg Museum für Naturkunde Görlitz. 15 records from Herbario XAL del Instituto de Ecología, A.C., México (IE-XAL). 64 records from Herbario IEB del Instituto de Ecología, A.C., México (IE-BAJíO). 6 records from CeDoc de Biodiversitat Vegetal: BCN-Seeds. 31 records from Dorset Sites of Nature Conservation Interest (SNCI) species records 2000-2008. 1 records from FKSE-Herbarium specimens of Faculty of Symbiotic Systems Science, Fukushima University, Japan. 23 records from Royal Botanic Garden Edinburgh Living Plant Collections (E). 2 records from Angiospermatatophytina Collection of Saitama Museum of Natural History. 455 records from svalbardflora.no. 180 records from Tiroler Landesmuseum Ferdinandeum. 1 records from The Fungal Collection at the Botanische Staatssammlung München. 43 records from The Vascular Plant Collection at the Botanische Staatssammlung München. 306 records from IBF Monitoring of Vascular Plants. 2 records from Inventario florístico de los cerros San Martí y El Patol en el semidesierto queretano. 375 records from Tropicos Specimen Data. 16 records from Nature Conservancy Council Berkshire Meadows Survey 1984-87 (as held by Thames Valley Environmental Records Centre). 56 records from BRERC species records recorded over 15 years ago. 530 records from Natural History Museum (London) Collection Specimens. 148 records from Catálogo Florístico Histórico de Navarra. Gobierno de Navarra. 7 records from Natural History Museum, Vienna - Herbarium W. 2 records from Lista florística preliminar de Tamaulipas. 3 records from Las especies endémicas de plantas en el estado de Jalisco, su distribución y conservación. 152 records from Computarización del Herbario ENCB, IPN. Fase IV. Base de datos de la familia Pinaceae y de distintas familias de la clase Magnoliopsida depositadas en el Herbario de la Escuela Nacional de Ciencias Biológicas, IPN. 2 records from Flora acuática vascular de las regiones hidrológicas R66 (Lagos Cráter del Nevado de Toluca) y R67 (Río Amacuzac-Lagunas de Zempoala), México. 3 records from Análisis de la heterogeneidad ambiental y conectividad de las áreas naturales del sur del Valle de México. 136 records from Flora-On: occurrence data of the flora of mainland Portugal. 3 records from Análisis de la heterogeneidad ambiental y conectividad de las áreas naturales del sur del Valle de México_1. 58 records from Ireland's BioBlitz. 2 records from Catálogos florísticos de México por entidad federativa e información etnobotánica de la Colección del Herbario Nacional Biól. Luciano Vela Gálvez (INIF). 6 records from Florística de áreas protegidas en el estado de Durango. 27 records from Base de datos sobre la flora de Durango. 2 records from Catálogo y base de datos preliminar de la flora de Sinaloa. 15 records from Universidad de Barcelona. Grup dInvestigació Geobotánica i Cartografia de la Vegetació. 5 records from KNWR Herbarium Collection. 2 records from East Ayrshire Species Database. 443 records from Phase Two Lowland Heathland Survey. 150 records from NMNH Extant Specimen Records. 4 records from Universität Salzburg. 1751 records from The Himalayan Uplands Plant database (HUP Version 1). 284 records from Canadian Museum of Nature Herbarium. 601 records from Vascular Plant Collection - University of Washington Herbarium (WTU). 21 records from The AAU Herbarium Database. 76 records from Herbarium (ICEL). 44 records from Herbarium (AMNH). 614 records from Observational database of Icelandic plants. 32 records from Colección de plantas vasculares del herbario de la Universitat de València (VAL).. 127 records from Herbario de Plantas Vasculares de la Universidad de Salamanca: SALA. 123 records from CSIC-Real Jardín Botánico-Colección de Plantas Vasculares (MA). 57 records from Universidad del País Vasco/EHU, Bilbao: Herbario BIO. 48 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO. 14 records from Jardín Botánico de Córdoba: Herbarium COA. 83 records from Aranzadi Zientzi Elkartea. 9 records from Universitat de Girona: HGI-Cormophyta. 13 records from CIBIO, Alicante:ABH-GBIF. 16 records from Herbarium of Vascular Plants Collection of the University of Extremadura (Spain). 8 records from Herbario de la Universidad de Sevilla. 39 records from Herbario HSS Finca La Orden-Valdesequera (CICYTEX). Gobierno de Extremadura. 245 records from Institut Botanic de Barcelona, BC. 153 records from Herbarium of Jyväskylä University Museum. 2 records from Caracterización de flora, edafofauna epígea, anfibios y aves del Complejo Páramos Chilí - Barragán, Tolima. 17 records from Plant Specimens of Kurashiki Museum of Natural History. 392 records from Vascular Plant Collection. 17 records from Botany registration database by Danish botanists. 1 records from Priest Pot species list, Cumbria, Britain. 14 records from Botanical Museum, Denmark. Database of registrations of red listed plants. 40 records from DAV UC Davis Center for Plant Diversity. 23 records from Herbarium (UNA). 17 records from Actualización de las bases de datos del Herbario XAL. Fase III. 25 records from Herbarium Berolinense. 1 records from Herbarium Willing. 5 records from PonTaurus collection. 904 records from Observations du Conservatoire botanique national du Bassin parisien.. 61 records from Biologiezentrum Linz. 9 records from United States National Plant Germplasm System Collection. 3 records from The Erysiphales Collection at the Botanische Staatssammlung München. 93 records from USU-UTC Specimen Database. 11 records from Institut Botanic de Barcelona, BC-Histórico. 12 records from Herbarium de Geo. B. Hinton, México. 1227 records from Harvard University Herbaria. 853 records from Vascular plants of south-central China. 9 records from Specimen Database of Colorado Vascular Plants. 128 records from inatura - Erlebnis Naturschau Dornbirn. 113 records from Herbarium Specimens of Museum of Nature and Human Activities, Hyogo Prefecture, Japan. 5 records from Kochi Prefectural Makino Botanical Garden. 88 records from SER Site-based Surveys. 6 records from English Nature Berkshire SSSI Records. 92 records from Commissioned surveys and staff surveys and reports for Scottish Wildlife Trust reserves - Verified data. 6 records from Herbario de la Universidad de Arizona, EUA. 12 records from Repatriación de datos del Herbario de Arizona (ARIZ). 53 records from Vascular Plants, Observations, Oslo (O). 5 records from FloVegSI - Floristical and fitocenological database of ZRC SAZU. 1 records from Schlern - (Bozen). 5 records from GEO Hauptveranstaltung Tirol (Innsbruck). 2 records from NSG Karwendel. 1 records from Cuxhavener Küstenheiden. 1 records from Gurgltal (Tarrenz). 1 records from Wald am Schloss Wittgenstein Bad Laasphe. 1 records from Feriendorf des Kreises Groß-Gerau/Ober-Seemen. 18 records from Vegetation surveys of coastal shingle in Great Britain. 48 records from Plantae, TAIF (Taiwan e-Learning and Digital Archives Program, TELDAP). 683 records from Atlas Flora Danica. 93 records from Phase 2 lowland peatland survey of Wales 2004 onwards. 3558 records from Scottish SNH-funded BSBI records. 7 records from Herbarium of Namur. 2 records from Natural History Museum, University of Tartu. 29 records from Herbarium of Umeå University (UME). 243 records from Base de datos de plantas vasculares del País Vasco: ARAN-EH. 408 records from Field Museum of Natural History (Botany) Seed Plant Collection. 106 records from NRW Regional Data: North Wales. 4 records from MPM Milwaukee Public Museum Herbarium. 285 records from Belgian IFBL Flora Checklists (1939-1971). 13 records from Tycanol National Nature Reserve (NNR) Species Inventory. 277 records from Inventaire National du Patrimoine Naturel : Flore Franco-Belge. 294 records from Colorado State University Herbarium. 228 records from R. L. McGregor Herbarium Vascular Plants Collection. 9 records from EDIT - ATBI in Mercantour/Alpi Marittime (France/Italy). 7 records from Herbario de la Universidad Pública de Navarra, Pamplona: UPNA-H. 212 records from Vascular Plant Specimen Database of Kanagawa Prefectural Museum of Natural History. 108 records from Gunma Museum of Natural History, Vascular Plant Specimen. 1 records from Artenvielfalt am Schlern. 2 records from Vom Gipfel ins Moor, Transekt im NSG Allgäuer Hochalpen. 13 records from Jardín Botánico Atlántico, Gijón: JBAG. 14 records from MGC Herbarium of University of Malaga (Spain): MGC-Cormof dataset. 95 records from Biological and palaeontological collection and observation data MNHNL. 82 records from Botany Division, Yale Peabody Museum. 55 records from Herbarium Senckenbergianum (FR). 1059 records from Vascular plants in power line clearings and the nearby forest, southeast Norway. 44 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO-Briof. 29 records from Database of Native Plants in Taiwan. 3 records from E39 Lyngdal - Ålgård. 47 records from Herbarium of Taiwan Forestry Research Institute. 69 records from Etapa final de la captura y catalogación del Herbario del Instituto de Ecología, AC, Centro Regional del Bajío. 9 records from Banco de datos florísticos del Herbario CHAP. 5 records from WII Herbarium Dataset. 78 records from National vegetation diversity inventory and mapping plan. 116 records from VIT Herbarium - Vascular Plants (The Natural History Museum of Alava). 17 records from Vascular Herbarium, NMBU. 1753 records from National Wetland Inventory (NV). 2366 records from FloraCAT: Banco de datos de los cormófitos de Cataluña. 1 records from Herbarium specimens, Harmas J.H. Fabre (FABR - Sérignan-du-Comtat) of the Muséum national d'Histoire naturelle (MNHN - Paris). 2 records from Faun. 993 records from Flora d'Andorra. 7 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Verified data. 22 records from National System of Protected Areas in Poland - Plants. 62 records from Rotherham Biological Records Centre - Non-sensitive Records from all taxonomic groups. 20 records from ArtenFinder. 1899 records from Lund Botanical Museum (LD). 8 records from Plantas vasculares de la Sierra Tarahumara -listado florístico, etnobotánico e histórico-. 1326 records from Natural Resources Wales Regional Data : Mid-Wales. 329 records from Geographically tagged INSDC sequences. 16 records from Plant Specimen from Herbarium (LBG) in China, Lushan Botanical Garden, Jiangxi and Chinese Academy of Sciences. 4581 records from Norwegian Species Observation Service. 37 records from University of Manitoba Herbarium (WIN) - Vascular Plant Collection. 14 records from Vascular Plants, Museum of Archaeology, University of Stavanger. 77 records from Plant Specimen from Herbarium (IBK) in China, Guangxi Institute of Botany, Chinese Academy of Sciences. 6 records from The vascular plants collection (P) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 1 records from Plants and Bryophytes recorded on Schiehallion 25-30 June 2000. 311 records from LERN Records. 102 records from Hatikka Observation Database. 309 records from Carnet en Ligne. 2 records from Flora vascular y endemismos de las partes altas de varios macizos montañosos de Querétaro y norte de Michoacán-1ra Fase. 15 records from SER Species-based Surveys. 8 records from ARKO kulturmarkseng. 3 records from Actualización de la base de datos sobre la flora de la Reserva de la Biósfera Sierra de Manantlán, Jalisco-Colima, México. 207 records from Royal Botanic Garden Edinburgh Herbarium (E). 17 records from Inventaire National du Patrimoine Naturel : Espèces Végétales Menacées de France métropolitaine. 1143 records from Waarnemingen.be - Plant occurrences in Flanders and the Brussels Capital Region, Belgium. 5 records from Michigan State University Herbarium Vascular Plants. 17 records from TWIC Biodiversity Field Trip Data (1995-2014). 10 records from Estudio florístico de la Sierra de Pachuca, Hidalgo, México. 2 records from Botany (UPS). 10 records from Data from Defra Family Organisations supplied to Staffordshire Ecological Record. 2 records from Merseyside BioBank (verified). 30 records from Herbier du Québec (QUE) - Collection de plantes vasculaires. 2 records from Banco de Germoplama del Jardín Botánico de Castilla-La Mancha. 244 records from Flora of Worcestershire. 11 records from Computarización del Herbario ENCB. Fase I (Base de datos de los ejemplares del Valle de México). 51 records from Estonian Nature Observations Database. 1 records from University of Amsterdam (NL) - Páramo vegetation research, Central Andean Cordillera - Colombia. 328 records from Inventaire National du Patrimoine Naturel : Flore d'Ille-et-Vilaine. 1 records from Herbier Flora selecta exsiccata publié par Ch. MAGNIER (BOUM). 2 records from Herbier E. P. Larchevêque (BOUM). 1289 records from Finnish Floristic Database (Literature Sources). 1 records from Base de datos computarizada del herbario CIB, Instituto de Investigaciones Biológicas, Universidad Veracruzana. 7 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 4 records from Welsh Invertebrate Database (WID). 7 records from Verneplan Hjerkinn karplanter. 1005 records from Vascular plant herbarium, Tromsø Museum. 1346 records from Vascular plant herbarium, NTNU University Museum. 764 records from Données ONF Faune-Flore-FOnge. 71 records from Institute of Ecology and Evolutionary Biology, National Taiwan University. 4637 records from Vascular Plants, Field notes, Oslo (O). 177 records from The New York Botanical Garden Herbarium (NY) - Vascular Plant Collection. 1848 records from Sistema de Información de la vegetación Ibérica y Macaronésica. 6 records from Distribution of Higher Plants in Greater Manchester. 219 records from Vegetation data from protected areas in Denmark (§ 3 in the Danish Nature Protection Act). 764 records from Données ONF Faune-Flore-FOnge. 32 records from Universidad de Navarra, Herbarium: PAMP-Vascular Plants. 35 records from Ecofact. 129 records from Green Plant Herbarium (TRT). 262 records from Inventaire National du Patrimoine Naturel : Flore du Massif Armoricain. 2 records from Stackpole National Nature Reserve Species Inventory and Ad Hoc sightings from around Pembrokeshire. 7 records from Dataset of herbarium specimens of threatened vascular plants in Catalonia. 12 records from Actualización e incremento de la base de datos del Herbario de la Benemérita Universidad Autónoma de Puebla. 2 records from Plants, Bryophytes and Lichens recorded on Quinag in 2006-2007. 2 records from Inventario florístico de la Reserva de la Biosfera Mariposa Monarca, México. 2 records from Plant Observation Records of Japan. 557 records from Floristic Databases of Mecklenburg-Pomerania - Higher Plants. 1 records from Herbarium of University of Białystok - Vascular Plants. 18 records from A grid-based database on vascular plant distribution in the Meshchera National Park, Vladimir Oblast, Russia. 1 records from Korean Peninsula Flora. 6 records from BioFresh Pond Data. 4 records from Gipuzkoako Foru Aldundiaren Landareen Germoplama Bankua / Banco de Germoplasma Vegetal de la Diputación Foral de Gipuzkoa. 12 records from English Nature Oxfordshire Fen Survey 1990-1991 (A Comparative Survey of Rich Calcareous Fens of Oxfordshire) (as held by Thames Valley Environmental Records Centre). 8 records from Digitization of plant specimens from Rhoen and Vogelsberg (FULD). 2071 records from Vascular Plant Herbarium, Oslo (O). 1 records from Herbarium specimens of Jardins botaniques and Conservatoire Botanique of Nancy (NCY). 4 records from Local Wildlife Site Surveys Oxfordshire. 213 records from Environmental Monitoring Database Species data 1987 to 2015. 8073 records from Flora von Deutschland (Phanerogamen). 1 records from Vascular plants of Amrum 2007-2008. 151 records from Suffolk Biodiversity Information Service (SBIS) Dataset. 27 records from WTSWW Data: All Taxa (West Wales). 47 records from E. C. Smith Herbarium (ACAD). 10 records from Sistematización del Herbario Nacional Forestal Biól Luciano Vela Gálvez. 23 records from Herbario de Plantas Vasculares de la Asociación BIGA para el estudio del patrimonio natural de Galicia: FBIGA. 7 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on the Sandwood Estate during 1998 â 2006.. 3 records from Artskartlegging flomsikringstiltak, Kvam 2013. 144 records from National Trust for Scotland Species Records. 1388 records from Vascular plant field notes, NTNU University Museum. 10292 records from Finnish Floristic Database (Finnish Museum of Natural History Collections). 1 records from Plants, Bryophytes and Lichens recorded on the Nevis Estate during summer 2003.. 20 records from Geneva Herbarium – General Collection (G). 5 records from English Nature and NCC Oxfordshire Surveys. 1556 records from Welsh BSBI data (ex-VPDB dataset) at hectad resolution. 4 records from Nijmegen Natural History Museum (NL) - Herbarium. 10 records from BRERC species records within last 15 years. 3 records from Flora of the Stołowe Mts.. 747 records from Some Plant Specimens from PE Herbarium in China from 1900 to 1950. 40 records from CAS Botany (BOT). 10 records from Atlas des plantes vasculaires de Lorraine. 23 records from University of Graz, Institute of Plant Sciences - Herbarium GZU. 7 records from NCC Berkshire Grassland Survey 1984-1987. 2 records from HEPH - Herbário Ezechias Paulo Heringer. 32 records from Vascular Plant Records up to 2010. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences